2020
DOI: 10.31234/osf.io/43fcg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How anxiety predicts interpersonal curiosity during the COVID-19 pandemic: The mediation effect of interpersonal distancing and autistic tendency

Abstract: With the world-wide implementation of quarantine to suppress the spread of the COVID-19, people, having weathering a hard time, are confronted with an alarming state of mental health. For people who have taken self-quarantine at home for a long time, the anxiety and the new “staying home normality” may undermine their desire to seek information and thus might have negative effects on their curiosity. Here, we explored and examined how anxiety and the effect of quarantine regulations during the public health em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…This finding supports those from other researchers of a relationship between the social network and curiosity (Thomas and Vinuales, 2017). Lastly, the fact that curiosity was significantly predicted by anxiety adds to recent research which revealed that COVID-19 restrictions may have affected the relationship between anxiety and interpersonal curiosity (Huang et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This finding supports those from other researchers of a relationship between the social network and curiosity (Thomas and Vinuales, 2017). Lastly, the fact that curiosity was significantly predicted by anxiety adds to recent research which revealed that COVID-19 restrictions may have affected the relationship between anxiety and interpersonal curiosity (Huang et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…A negative correlation was found between social anxiety and general social curiosity, and a positive correlation was found between social anxiety and covert social curiosity (Renner, 2006). During the Covid-19 pandemic, it was found to be negative correlations between interpersonal distancing and interpersonal curiosity (Huang et al, 2021). In addition, the interpersonal curiosity scale was developed by Litman and Pezzo (2007), and the social curiosity scale was developed by Renner (2006).…”
Section: Introductionmentioning
confidence: 99%